»Verantwortung vor Gott« und andere Koordinaten: Zur Präambel der EU-Verfassung - Brandt, Reinhard (Zeitschrift für Theologie und Kirche, 2006)
If the constitution of the EU is going to be reviewed again, the question of the missing reference to God in the preamble should be discusses anew. This article points out that the preamble is by no means neutral with regard to ideology, but that it is bound to a certain ideology. It also makes suggestions as to how the active sharing of different religions and ideologies can be embodied in the constitution.